Ideology and myth: a critical reflection - Ansión, Juan (1985)
The theoretical reflection that is presented responded to a need: to formulate a conceptual criticism that would allow the contributions of Marxism and cultural anthropology to be used for the study of Ayacucho stories. Mythical thought is not a mere "falsification" of reality as a common interpretation of the Marxist tradition implies. A review of the approaches of Marx and Engels, and of later authors, culminates in a conceptualization of its own that points out clues to the study of mythical thought and of the way of thinking, of cultural shock and syncretism.